Comportamento violento, bullying e atividade física em adolescentes - Oliveira, Mona Gizelle Dreger de (2018)
Introduction: Violent behaviour and bullying are present among adolescents and their association between physical activity and sports practice isn't clear. So, this study aims to verify the association between violent behaviour and the practice of physical and sports activity among adolescents. Methodology: The study was divided in two steps organized as follows: the first one was to analyse the association between sports practice and the determinants of violent behaviour in adolescents from Aracaju and Metropolitan Region, while that the second one, based on the National Survey of School Health 2015 (PeNSE/2015), aimed to analyse the association between bullying behaviour and physical activity accumulated in adolescent’s students in Brazil. These steps resulted in two manuscripts submitted for publication to periodicals ranked in area 21 of CAPES. Results: The first study showed a greater chance of violent behaviour in males (OR = 3.0, 95%CI 2.3 - 3.9), individuals that reported alcohol consumption (OR = 2.5, 95%CI, 9 - 3.3) and cigarette consumption (OR = 2.6, 95%CI 1.7 - 4.0). In addition, it was observed that sports practice increase 40% the chance of violent behaviour when compared to individuals who do not practice sports (OR = 1.4; 95%CI 1.1 - 1.8). For the second manuscript, considering the stratification in "active" and "less active" for physical activity accumulated, a binary logistic adjusted model analysis for each stratum and the variable "perpetrating bullying" as outcome; was verified an association between perpetrating bullying and male sex (OR = 2.21, 95%CI 1.81 - 2.67) and to become victim from self-perceived bullying (OR = 2.45, 95% CI 2.05 - 2.93) and concept of bullying (OR = 1.47; 95%CI 1.22 - 1.76). For the "less active" adolescents, there was an association between "perpetrating bullying" and sex male (OR = 1.88, 95% CI 1.65 - 2.13), elementary school (OR = 1.33, 95%CI, 2.56 - 3.36) and concept of bullying (OR = 1.43, 95%CI 1.25 - 1.64). Conclusion: Adolescents that practice sports are more likely to engage in violent behaviour and in both the "active" and "less active" groups perpetrators of bullying are more likely to have suffered bullying.